2016
DOI: 10.1159/000445839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tadalafil 5 mg Dosed Once Daily in Men with Premature Ejaculation

Abstract: Purpose: In this study, we evaluated the effect of 5 mg tadalafil once daily in men with premature ejaculation (PE). Methods: Thirty married men with lifelong PE and 30 healthy men as control group were included in this study. All the patients received 5 mg tadalafil once a day for a month. The international index of erectile function questionnaire and intravaginal ejaculatory latency times (IELTs) and PE profile were recorded before and after treatment. Plasma samples were collected before and after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…This finding was in agreement with Ozcan et al. (), who found that administration of 5 mg tadalafil once daily for 1 month was safe in the treatment of patients with lifelong PE and the most common side effects were headache, back pain, myalgia, dyspepsia and gastroesophageal reflux. Dell'Atti et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was in agreement with Ozcan et al. (), who found that administration of 5 mg tadalafil once daily for 1 month was safe in the treatment of patients with lifelong PE and the most common side effects were headache, back pain, myalgia, dyspepsia and gastroesophageal reflux. Dell'Atti et al.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was in agreement with Ozcan et al. (), who reported that administration of 5 mg tadalafil once daily for 1 month was effective in the treatment of patients with lifelong PE as it improved IELT and premature ejaculation profile. Karabakan, Keskin, Akdemir, and Bozkurt () found that administration of 5 mg tadalafil once daily for 3 months showed a significant increase in IELT and IIEF‐5 values of patients with ED and PE.…”
Section: Discussionsupporting
confidence: 92%
“…PDE5 inhibitors are frequently used in the treatment of ED and clinical studies have reported their positive effect on patients with PE ( 14 - 16 ). In a recent study, a daily dose of 5mg tadalafil has been shown to significantly increase IELT in patients diagnosed with lifelong PE ( 17 ). However, to our knowledge, there is no study in the literature that determined the effect of tadalafil 5mg daily on ejaculatory time in patients with ED.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study carried out by Özcan et al, it was determined that single-dose 5 mg tadalafil usage in males with premature ejaculation provides a significant increase in IELT by developing the ejaculation control perception, increasing sexual satisfaction, and being beneficial on the personal stress related to ejaculation. However, as noted by the authors, the role of PDE 5 inhibitors in premature ejaculation is controversial [16] .…”
Section: Discussionmentioning
confidence: 99%